Muscle function mediates the association between vitamin D deficiency and hip fracture risk: a retrospective study in older adults - Wang, Xiongyi; Hu, Yutong; Yun, Simin; Zhu, Keyu; Zheng, Miao; Wei, Qi; Pan, Sheng; Xu, Youjia (Frontiers in Endocrinology, 2025)
ObjectivesHip fracture, a critical public health concern in aging populations, are associated with significant morbidity, mortality, and disability and have been referred to as “the last fracture of life.” While vitamin D influences bone mineral density (BMD) and fragility fracture risk, its impact on muscle function and its relationship with fracture risk remains underexplored. This study aimed to investigate whether vitamin D deficiency increases hip fracture risk primarily through its effects on muscle function.MethodsIn this retrospective study, 138 patients aged ≥ 50 years with initial low-energy hip fracture treated between January 2024 and June 2024 were compared with 182 community residents aged ≥ 50 years recruited from the hospital physical examination center. Clinical baseline data such as age, sex, and body mass index (BMI), were recorded. Through regression analysis, independent factors influencing hip fracture risk were analyzed. The effects of vitamin D on BMD and muscle function were evaluated using femoral neck areal BMD (FN aBMD) and pectoralis muscle index (PMI), respectively.ResultsPatients with hip fracture were significantly older and had lower BMI, vitamin D level, muscle function, and FN aBMD than controls (P < 0.05). Univariate analysis identified age, BMI, vitamin D, PMI, and FN aBMD as key factors influencing hip fracture risk. After adjusting for age, sex and BMI, vitamin D, PMI, and FN aBMD emerged as independent protective factors against hip fracture in patients. Vitamin D was also found to be an independent protective factor against sarcopenia. However, Vitamin D levels did not significantly affect osteoporosis after adjusting for sex, age, and BMI. FN aBMD and PMI mediated 33.3% and 50.0%, respectively, of the association between vitamin D and HF.ConclusionsVitamin D deficiency is associated with an increased risk of hip fracture, primarily through its impact on muscle function rather than BMD. Although vitamin D supplementation is crucial in older adults, integrating muscle function assessments into fracture prevention strategies is essential.